(untitled) (The Research of Medical Science Review, 2025)
There are about 41.8% of the pregnant women are anemic in the world. It is an important public health issue among pregnant women especially in the developing countries such as Pakistan. The main objective of the present study was, therefore, to determine the frequency of anemia in pregnant women (aged between 15-47 years) who were attending for their antenatal visits at the Shaikh Khalifa bin Zaid Al-Nehyan Combined Military Hospital (SKBZ) of Muzaffarabad, Azad Jammu and Kashmir, Pakistan. A descriptive cross-sectional study was carried out from May to December 2023, on 100 pregnant women who were attending for their antenatal visits at the Combined Military Hospital of Muzaffarabad. Systematic random sampling technique was used to select the study subjects. Information about socio-economic and demographic characteristics, clinical or obstetric characteristics, consumption of the iron and iron containing sources of food were collected by using pretested, validated, structured and self-administered questionnaire and a checklist. Descriptive analysis by using means, standard deviation, range, frequency and percentages was computed. The Chi-square test (P- value<0.05) and odds ratio (OR) with 95% of the confidence interval (CI) was used to find the relationship between dependent and independent variables. The findings from this study revealed that the overall prevalence of anemia among in pregnant women was 42.0%. Of these, 16.7% of the participants were severely anemic, 45.2% of them were moderately anemic and the remaining 45.2% were mildly anemic. Reproductive health education and advice should be given to all the women to create awareness regarding risk factors that develop anemia in late pregnancy.